Intra-atrial Course of Right Coronary Artery: A Rare Anomaly Detected on Computed Tomography - Archita Mahajan; Mansi Verma; Sumala Kapila (Methodist DeBakey Cardiovascular Journal)
We describe a case of a 59-year-old male who presented with intermittent episodes of atypical chest pain where computed tomography revealed intracavitary course of right coronary artery.The recognition of intra-atrial course of RCA is important as it can predispose patients to inadvertent iatrogenic injuries during surgical or endovascular procedures that can prove catastrophic, even fatal.